A Review of Developmental Networks - Dobrow, Shoshana R.; Chandler, Dawn E.; Murphy, Wendy M.; Kram, Kathy E. (Journal of Management, 2012)
During the past decade, mentoring research has broadened from its traditional dyadic perspective to examine the support provided by a “developmental network.” This article reviews the literature on developmental networks—groups of people who take an active interest in and action toward advancing a protégé’s career. Building on positive organizational scholarship (POS) research on high-quality connections and relationships, the authors propose that a “mutuality perspective,” or taking the viewpoints of all members of the developmental network into account, is a notable gap in developmental network research. They apply this perspective to developmental networks research and discuss implications and avenues for future inquiry. As part of their review, the authors clarify the boundaries of the developmental network construct. They also identify and discuss four research streams that encompass extant studies of developmental networks. This article extends previous reviews of the broad field of dyadic mentoring by providing the first systematic review of developmental network research.